Isolasi Bakteri Indigineous dari Limbah Cair Tahu dalam Mendegradasi Protein dan Melarutkan Fosfat - Asril, Muhammad; Oktaviani, Indah; Leksikowati, Santi (Jurnal Teknologi Lingkungan, 2019)
ABSTRACTThe tofu industry in Indonesia is growing rapidly along with the consumption needs. This amount affects the production of the tofu wastewater that will be discharged into the environment. The waste contains high levels of BOD, COD, and high protein organic substances. The discharged of the tofu wastewater without going through a good process of separation and treatment caused odor and pollution in the water and the soil environment. This study aims to examine the amount of production, a chemical characteristic, and bacterial potential (the genus of Pseudomonas and Aeromonas, proteolytic bacterial isolates, and potential phosphate solvent bacteria) which can be used as a reference for bioconversion of higher tofu wastewater. The method used in this study was water sampling, chemical characteristic testing (BOD, COD, total protein, and pH), the bacterial isolation of Pseudomonas and Aeromonas using GSP media, isolation of proteolytic bacteria using nutrient agar + Skim milk media and testing the solubilizing phosphate ability in pikovskaya media. The results showed the production of the tofu liquid waste reached 4000 liters/day with BOD, COD, total protein and pH content is 3210 mg/ L, 7102 mg/L, 20.74% and 5, respectively. The amount of indigenous bacteria in wastewater from Pseudomonas were 72 x 102 cfu/ml), Aeromonas were 18 x 102 cfu/ml), and total proteolytic bacteria were 23.7 x 105 cfu/ml). Proteolytic bacteria obtained in this research were 28 isolates with diverse proteolytic abilities. In addition, 17 of the 28 proteolytic bacteria isolates have the ability to soluble phosphate on pikovskaya medium. These results show that the production of the tofu liquid waste is quite high. Therefore, the chemical character and the presence of bacteria in it have the potential to be developed and can be used as a reference for bioconversion of waste before being discharged into the environment.Keywords: Aeromonas, proteolytic bacteria, tofu wastewater, phosphate solubilizing bacteria, Pseudomonas ABSTRAKIndustri tahu di Indonesia berkembang sangat pesat seiring dengan kebutuhan konsumsi masyarakat Indonesia. Jumlah ini berpengaruh terhadap produksi limbah cair tahu yang akan dibuang ke lingkungan. Limbah tersebut memiliki kandungan BOD, COD dan bahan organik berupa protein yang cukup tinggi. Limbah cair tahu jika dibuang lingkungan tanpa melalui proses pemisahan dan perlakuan yang baik dapat menimbulkan bau dan pencemaran di lingkungan air dan tanah. Penelitian ini bertujuan untuk mengkaji jumlah produksi, karakteristik kimia dan potensi biologi (bakteri genus Pseudomonas dan Aeromonas, isolat bakteri proteolitik dan bakteri pelarut fosfat potensial) yang nantinya dapat digunakan sebagai acuan biokonversi limbah cair tahu yang semakin tinggi. Metode yang digunakan pada penelitian ini adalah pengambilan sampel, pengujian karakteristik kimia (BOD, COD, total protein dan pH), isolasi bakteri genus Pseudomonas dan Aeromonas pada media GSP, isolasi bakteri proteolitik di media Nutrien agar + Skim milk dan pengujian kemampuan melarutkan fosfat pada media pikovskaya. Hasil menunjukkan bahwa limbah cair yang diproduksi setiap harinya mencapai 4000 liter/hari dengan kandungan BOD, COD, total protein dan pH berturut-turut sebesar 3210 mg/L, 7102 mg/L, 20.74 % dan 5. Jumlah bakteri indigeous dalam limbah cair tahu dari genus Pseudomonas adalah 72 x 102 cfu/ml, genus Aeromonas adalah 18 x 102 cfu/ml dan total bakteri proteolitik adalah 23.7 x 105 cfu/ml. Bakteri proteolitik yang diperoleh berjumlah 28 isolat dengan kemampuan proteolitik yang cukup beragam. Selain itu, 17 dari 28 isolat bakteri proteolitik tersebut memiliki kemampuan melarutkan fosfat pada media pikovskaya. Hasil ini menunjukkan bahwa produksi limbah cair tahu yang cukup tinggi, karakteristik kimia serta keberadaan bakteri didalamnya memiliki potensi untuk dikembangkan dan dapat dijadikan sebagai acuan untuk biokonversi limbah sebelum dibuang ke lingkungan.Kata kunci: Aeromonas, bakteri proteolitik, limbah cair tahu, bakteri pelarut fosfat, Pseudomonas